KONSORSIA BAKTERI PENGURAI SIANIDA YANG DI ISOLASI DARI BUANGAN INDUSTRI PENGOLAHAN EMAS - Sulistinah, Nunik; Sunarko, Bambang (Jurnal Teknologi Lingkungan, 2010)
Bacterial consortium capable of growing and utilizing cyanide as a source of nitrogen were isolated from effluent of gold mining industry. The isolation was conducted using liquid enrichment medium with potassium cyanide and glucose as nitrogen and carbon source, respectively. These consortium could tolerate and were able to grow on KCN at concentration of up to 1000 ppm. Bacterial consortium LP3 were also able to degrade potassium cyanide and ammonium as product of the degradation. The degradation rate was 9,0μM per minute. The cyanide-degrading bacteria found in this consortium were identified as Bacillus, Corynebacterium, and Serratia.Keywords: potassium cyanide, nitrogen source, bacterial consortium LP3,degradation